PROFESIONALIZACIÓN DE LA ENFERMERÍA Y DESEMPEÑO, DESDE LA ÓPTICA DEL JEFE INMEDIATO SUPERIOR EN CHIHUAHUA, CHIHUAHUA - Eliazar González Carrillo; Ana María Arras Vota (European Scientific Journal, ESJ, 2014)
An academic institution needs to determine the impact of the programs they offer; this is the case of the professionalization in nursing. For decades nursing has developed knowledge, theories and models that have contributed to the improvement of professional practice in the different fields of action for nursing. One way to learn about the outcome of an educative program is throught the results in their graduates such as improvment of status, position, salaries and satisfaction at work. The objective of this study is to analyze the perception of the professional performance of graduates form the academic program offered by the Faculty of Nursing and Nutrition of the Autonomous University of Chihuahua from the perspective of the immediate supervisor. The study is transversal and of a descriptive nature. 46 immediate chiefs of the graduates answered a questionare designed in Likert´s format. It is also important to stress that these actors were from three public institutions and one of the private sector. The reliability of the instrument was measured with the alpha of cronbach with an outcome value of 0.82. Results reveal that immediate chiefs considered that 92.0% of the graduates of the program obtained knowledge, 80% changed attitudes and skills to provide patient´s care, 97.4% respect hierarchical authority and 74.3% uses the nurse process as requiered by the profession. Therefore, it can be said that the studied program contributed with the needed elements for the professional practice.